Students’ Perception and Exploring Technological Roles in Solid Waste Engineering and Management Education - Khairuddin, Dzulaikha; Nik Ali, Nik Hakimi; Kamaruding, Musmuliadi; Ismail, Norfarah Nadia (International Journal of Sustainable Construction Engineering and Technology, 2024)
A comprehensive understanding of students' perceptions within the Solid Waste Engineering and Management course contributes valuable insights to educators, institutions, and policymakers, facilitating the enhancement of waste management education through enriched teaching methods and technology integration that align with students’ evolving needs. This study investigates students’ perceptions in the context of the Solid Waste Engineering and Management course, analyzing demographic characteristics, impressions, lecturer professionalism, teaching and learning activities, and technology utilization. The sample encompasses diverse age groups, genders, semesters, and educational backgrounds, enhancing the study’s comprehensiveness. Employing a quantitative approach, the research combines a survey questionnaire with statistical analyses. Descriptive statistics and correlation analysis unveil intricate relationships among variables and perceptions, offering nuanced insights. The results reveal positive impressions among students regarding knowledge enhancement, content relevance, increased confidence, and effective assessment methods. Lecturer professionalism is highlighted through attendance monitoring, academic guidance, and language use. Teaching and learning activities garner favorable responses, with active involvement, effective explanations, and challenging delivery styles appreciated. Technology’s role in enhancing engagement and leveraging online resources is acknowledged. Correlation analysis underscores the strong associations between lecturer professionalism and effective teaching, learning activities, and course impression. Positive perceptions of teaching and learning activities correlate with a positive course impression.